2021
DOI: 10.3892/etm.2021.10882
|View full text |Cite
|
Sign up to set email alerts
|

Identification and functional annotation of differentially expressed long noncoding RNAs in retinoblastoma

Abstract: Retinoblastoma (RB), the most common intraocular malignancy, typically occurs in pediatric patients under the age of 6 years. The present study aimed to explore the long noncoding RNA (lncRNA) expression profile in RB and identify novel lncRNA biomarkers to facilitate the investigation of molecular mechanisms of RB and improve clinical therapy. Raw microarray data for the comparison of gene expression between three RB and three adjacent normal tissue samples were downloaded from Gene Expression Omnibus (datase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Previous microarray and bioinformatics analysis on RB tumor specimens revealed that the above enriched terms were associated with RB tumor occurrence, development, and chemo-resistance by regulating cell growth, cell survival, and proliferation. 22 , 29 , 30 Several studies have demonstrated that the neuroactive ligand–receptor interaction pathway is linked to a poor prognosis in various cancers, and breast cancer patients with low expression of cannabinoid receptor 1 (CNR1, part of this pathway) may benefit from chemotherapy. 31 Bioinformatics analysis of gene expression data of RB tumor tissues compared to normal retina revealed that the aberrantly expressed protein coding genes and target genes for DE lncRNAs are enriched for neuroactive ligand–receptor interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous microarray and bioinformatics analysis on RB tumor specimens revealed that the above enriched terms were associated with RB tumor occurrence, development, and chemo-resistance by regulating cell growth, cell survival, and proliferation. 22 , 29 , 30 Several studies have demonstrated that the neuroactive ligand–receptor interaction pathway is linked to a poor prognosis in various cancers, and breast cancer patients with low expression of cannabinoid receptor 1 (CNR1, part of this pathway) may benefit from chemotherapy. 31 Bioinformatics analysis of gene expression data of RB tumor tissues compared to normal retina revealed that the aberrantly expressed protein coding genes and target genes for DE lncRNAs are enriched for neuroactive ligand–receptor interaction.…”
Section: Discussionmentioning
confidence: 99%
“… 31 Bioinformatics analysis of gene expression data of RB tumor tissues compared to normal retina revealed that the aberrantly expressed protein coding genes and target genes for DE lncRNAs are enriched for neuroactive ligand–receptor interaction. 29 , 30 Moreover, this is one of the 50 pathways significantly enriched for DEGs between chemoresistance Y79 versus parental Y79 cells. 32 MicroRNAs in cancer were enriched only for DE genes of TR-RB.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is necessary to identify new RB-specific biomarkers, elucidate their molecular mechanisms and develop improved RB-targeted therapeutic strategies. 114 RB is caused by the biallelic deletion of the tumour suppressor gene RB transcriptional co-repressor 1 (RB1) in 98% of cases, whereas 2% of cases have normal RB1 levels in tumours initiated by amplification of the MYCN oncogene. 115 An increasing number of studies have shown that the Hippo pathway is important in RB.…”
Section: Rbmentioning
confidence: 99%
“…115 An increasing number of studies have shown that the Hippo pathway is important in RB. 114,116 Reduced LATS2 levels can strongly inhibit the induction of cellular senescence by RB protein. 117 TAZ is highly expressed in RB tissues, and TAZ downregulation can inhibit retinoblastoma cell proliferation and block cell cycle progression.…”
Section: Rbmentioning
confidence: 99%
See 1 more Smart Citation